The Phytophthora infestans Haustorium Is a Site for Secretion of Diverse Classes of Infection-Associated Proteins - Shumei Wang (American Society for Microbiology, 2018)
ABSTRACT The oomycete potato blight pathogen Phytophthora infestans secretes a diverse set of proteins to manipulate host plant immunity. However, there is limited knowledge about how and where they are secreted during infection. Here we used the endoplasmic reticulum (ER)-to-Golgi secretion pathway inhibitor brefeldin A (BFA) in combination with liquid chromatography-electrospray tandem mass spectrometry (LC-MS/MS) to identify extracellular proteins from P. infestans that were conventionally secreted from in vitro-cultured hyphae. We identified 19 proteins with predicted signal peptides that potentially influence plant interactions for which secretion was attenuated by BFA. In addition to inhibition by the apoplastic effector EPIC1, a cysteine protease inhibitor, we show that secretion of the cell wall-degrading pectinesterase enzyme PE1 and the microbe-associated molecular pattern (MAMP)-like elicitin INF4 was inhibited by BFA in vitro and in planta, demonstrating that these proteins are secreted by the conventional, Golgi-mediated pathway. For comparison, secretion of a cytoplasmic RXLR (Arg-[any amino acid]-Leu-Arg) effector, Pi22926, was not inhibited by BFA. During infection, whereas INF4 accumulated outside the plant cell, RXLR effector Pi22926 entered the plant cell and accumulated in the nucleus. The P. infestans effectors, the PE1 enzyme, and INF4 were all secreted from haustoria, pathogen structures that penetrate the plant cell wall to form an intimate interaction with the host plasma membrane. Our findings show the haustorium to be a major site of both conventional and nonconventional secretion of proteins with diverse functions during infection. IMPORTANCE There are many different classes of proteins secreted from Phytophthora infestans that may influence or facilitate infection. Elucidating where and how they are secreted during infection is an important step toward developing methods to control their delivery processes. We used an inhibitor of conventional secretion to identify the following different classes of infection-associated extracellular proteins: cell wall-degrading and cell wall-modifying enzymes, microbe-associated molecular pattern-like proteins that may elicit immune responses, and apoplastic effectors that are predicted to suppress immunity. In contrast, secretion of a cytoplasmic effector that is translocated into host cells is nonconventional, as it is insensitive to inhibitor treatment. This evidence further supports the finding that proteins that are active in the apoplast and effector proteins that are active in the host cytoplasm are differentially secreted by P. infestans. Critically, it demonstrates that a disease-specific developmental structure, the haustorium, is a major secretion site for diverse protein classes during infection.